NATURAL TRANSFORM AND SPECIAL FUNCTIONS - Anil Dhondiram Chindhe; Sakharam Kiwne (Journal of New Theory)
Abstaract−The branch of integral transform attract many researcher in this field and hence various types of integral transforms are introduced. Natural transform is one of the newly defined transform which has wide range of applications in science and engineering field. In this paper we derived the Natural transform of some special functions